2019
DOI: 10.1175/jcli-d-18-0216.1
|View full text |Cite
|
Sign up to set email alerts
|

Arctic Summer Airmass Transformation, Surface Inversions, and the Surface Energy Budget

Abstract: 2019)Arctic summer airmass transformation, surface inversions, and the surface energy budget. Journal of Climate, 32 (3). pp. 769-789. ABSTRACTDuring the Arctic Clouds in Summer Experiment (ACSE) in summer 2014 a weeklong period of warm-air advection over melting sea ice, with the formation of a strong surface temperature inversion and dense fog, was observed. Based on an analysis of the surface energy budget, we formulated the hypothesis that, because of the airmass transformation, additional surface heating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 70 publications
(82 reference statements)
4
64
0
Order By: Relevance
“…The combination of low clouds trapped in a stable and warm lower troposphere led to large LTS and positive LWN. In ACSE this regime was primarily associated with an 8‐day event in early August (Tjernström et al, ), although stable, moist inversions did occur during other instances at ACSE (Tjernström et al, ) and climatologically occur with a modest frequency (Sedlar & Tjernström, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of low clouds trapped in a stable and warm lower troposphere led to large LTS and positive LWN. In ACSE this regime was primarily associated with an 8‐day event in early August (Tjernström et al, ), although stable, moist inversions did occur during other instances at ACSE (Tjernström et al, ) and climatologically occur with a modest frequency (Sedlar & Tjernström, ).…”
Section: Resultsmentioning
confidence: 99%
“…Detailed descriptions of the instrumentation and measurements are provided in Sotiropoulou et al (2016) and Tjernström et al (2019). We examine only a subset of the available observations.…”
Section: Acse Observationsmentioning
confidence: 99%
“…Warm-air advection episodes, although maybe not as extreme as the one analyzed in this study, occur frequently near the Arctic ice edge in summer, resulting in the development of surface temperature inversions over the melting sea ice . Tjernström et al (2018) found that these surface inversions can be further divided into two categories: (a) the "moist" ones, accompanied by surface humidity inversions and usually low clouds/fog, and (b) the "dry" ones, mainly associated with clear skies. These different atmospheric states are also found during the examined episode: an elevated inversion associated with elevated clouds was observed during the early days, while a strong surface inversion with an embedded fog persisted during the core event.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the conditions are right in this experiment setup for its genesis but do not favor its full development. Previous research has provided insight into such humidity inversions, revealing that they tend to form when precipitation removes humidity from an internal mixed layer while the residual layer above remains unchanged (Tjernström et al, , ). Decoupling from humidity sources above and below can help in this process (Loewe et al, ; Solomon et al, , ).…”
Section: Resultsmentioning
confidence: 99%
“…The processes controlling its evolution cover a broad range of scales (e.g., Curry et al, ). In addition, a distinction can be made between locally driven processes and more remotely controlled processes (Tjernström et al, ). Local processes act mostly on small scales and include the surface exchange of heat and humidity, vertical mixing by turbulence driven by cloud top cooling (Shupe et al, ), the microphysics of mixed‐phase clouds and their sensitivity to condensation nucleii (Ovchinnikov et al, ; Solomon et al, ), and the degree of coupling of the AML to the surface (e.g., Brooks et al, ; Solomon et al, , ).…”
Section: Introductionmentioning
confidence: 99%